Is Pre-operative Quadriceps Strength a Predictive Factor for the Outcomes of Anterior Cruciate Ligament Reconstructions - Qiu, Jihong; He, Xin; Fu, Sai-Chuen; Ong, Michael Tim-Yun; Teng Leong, Hio; Shu-Hang Yung, Patrick (International Journal of Sports Medicine, 2020)
Persistent quadriceps weakness prevents patients from returning to sports after ACL reconstruction. Pre-operative quadriceps strength was indicated as an important factor for the outcomes of ACL reconstruction. However, the existing evidence is controversial. Therefore, this systematic review was conducted to summarize and evaluate the relationship between pre-operative quadriceps strength and the outcomes following ACL reconstruction, and to summarize the predictive value of pre-operative quadriceps strength for satisfactory post-operative outcomes. Pubmed, WOS, Embase, CINAHL and SportDiscus were searched to identify eligible studies according to PRISMA guidelines. Relevant data was extracted regarding quadriceps strength assessment methods, pre-operative quadriceps strength, participants treatment protocols, post-operative outcomes, follow-up time points and the relevant results of each individual study. Twelve cohort studies (Coleman methodology score: 62±10.4; from 44–78) with 1773 participants included. Follow-up period ranged from 3 months to 2 years. Moderate evidence supports the positive association between pre-operative quadriceps strength and post-operative quadriceps strength; weak evidence supports the positive association between pre-operative quadriceps strength and post-operative functional outcomes. By now, there is no consensus on the predictive value of pre-operative quadriceps strength for achieving satisfactory quadriceps strength after ACLR. To conclude, pre-operative quadriceps strength should be taken into consideration when predict patient recovery of ACLR.
Keywords: anterior cruciate ligament; quadriceps strength; systematic review